An assessment of Polish women's level of knowledge about endometriosis: a pilot study - Joanna Szymańska; Magdalena Dąbrowska-Galas (BMC, 2021)
Abstract Introduction Insufficient knowledge about endometriosis among women is one of the causes of its delayed diagnoses. Due to the elusiveness of symptoms, the most important component of early detection is proper and exhaustive knowledge. The objective of the study was to assess Polish women's awareness of endometriosis. Methods The pilot studies were performed with the participation of 200 women, in an average age of 33.65 years (SD = 11.45), who completed the authors' questionnaire related to self-assessment of the level of knowledge about the disease, its symptoms, late effects and directions of a remediation procedure. The statistical analysis was performed using the IBM SPSS Statistics 25 suite. It included a frequency analysis, a one-way analysis of variance ANOVA, a single variable regression analysis and Student's t-test for independent samples. Results Almost 84% of women had heard about endometriosis, while only 1/3 of them considered their knowledge sufficient or good. Very good knowledge was declared by 4.5% of women, while 16.1% of participants had never heard about it. The level of knowledge was significantly higher (p = 0.001) among women with medical education. Polish women acquired their knowledge mainly from the Internet and the experience of other women. The reasons identified by women were the still existing 'taboo' related to menstruation, the absence of information in the media and education in schools, which is critical according to 92.4% of women. Conclusions Polish women's level of knowledge about endometriosis is insufficient, which we should strive to improve. Higher awareness is presented by women with medical education, and the higher the level of knowledge, the larger a woman's interest in healthy behaviour.